Advertisement Remove all ads

Prove that Cot X Cot 2x – Cot 2x Cot 3x – Cot 3x Cot X = 1 - Mathematics

Prove that cot x cot 2x – cot 2x cot 3x – cot 3x cot x = 1

Advertisement Remove all ads

Solution

L.H.S. = cot x cot 2x – cot 2x cot 3x – cot 3x cot x

= cot x cot 2x – cot 3x (cot 2x + cot x)

= cot x cot 2x – cot (2x) (cot 2x + cot x)

= cot x cot 2– (cot 2cot x – 1)

= 1 = R.H.S.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 11 Mathematics Textbook
Chapter 3 Trigonometric Functions
Q 22 | Page 74
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×